Hybrid and biocompatible cellulose/polyurethane nanocomposites with water-activated shape memory properties. (15th July 2019) - Urbina, Leire; Alonso-Varona, Ana; Saralegi, Ainara; Palomares, Teodoro; Eceiza, Arantxa; Corcuera, María Ángeles; Retegi, Aloña
Graphical abstract: Highlights: Biocompatible BC/WBPU nanocomposites with water-activated shape memory properties. BC wet membranes embedded and coated by the WBPU suggesting good affinity. Elastomeric BC/WBPU nanocomposites with enhanced modulus and strength BC induced to an improved shape fixity ratio and faster recovery process in water. Abstract: Water-activated shape memory bacterial cellulose/polyurethane nanocomposites were prepared by the immersion of bacterial cellulose (BC) wet membranes into waterborne polyurethane (WBPU) dispersions for different times. The high affinity between the hydrophilic BC and water stable polyurethane led to the coating and embedding of the BC membrane into the WBPU, facts that were confirmed by FTIR, SEM and mechanical testing of the nanocomposites. The mechanical performance of the nanocomposites resulted enhanced with respect to the neat WBPU, confirming the reinforcing effect of the BC membrane. An improvement of the shape fixity ability and faster recovery process with the presence of BC was observed. In 3 min, the nanocomposite with highest BC content recovered the 92.8 ± 6.3% of the original shape, while the neat WBPU only recovered the 33.4 ± 9.6%. The obtained results indicated that 5 min of impregnation time was enough to obtain nanocomposites with improved mechanical performance and fast shape recovery for potential biomedical applications. The present work provides an approach for developing environmentally friendly and biocompatible BC/polyurethane based materials with enhanced mechanical and shape memory properties.